2021
DOI: 10.3389/fphar.2021.643446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Danhong Injections at Different Time-points During the Perioperative Period of Acute Myocardial Infarction: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Objectives: Danhong injections (DHI) are widely used in the treatment of acute myocardial infarction (AMI). As there are no guidelines for the timing of DHI in the peri-percutaneous coronary intervention (PCI) period for AMI, we investigated the effects of DHI timing.Methods: We reviewed reports published before September 30, 2020 in PubMed, embase, the Cochrane Central Register of Controlled Trials, the Chinese BioMedical database, Chinese VIP database, Wanfang database, and Chinese National Knowledge Infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Through a systematic review and meta-analysis of randomized controlled trials, some studies have compared the efficacy of DHI at different time points in the perioperative period of acute myocardial infarction. The analysis included 23 studies, all of which showed that the efficacy of the DHI was better (He et al, 2021). Some researchers have meta-analyzed GDI in the adjuvant treatment of angina pectoris, including 41 randomized controlled trials involving 4,462 patients.…”
Section: Myocardial Infarction and Cardiomyopathymentioning
confidence: 99%
“…Through a systematic review and meta-analysis of randomized controlled trials, some studies have compared the efficacy of DHI at different time points in the perioperative period of acute myocardial infarction. The analysis included 23 studies, all of which showed that the efficacy of the DHI was better (He et al, 2021). Some researchers have meta-analyzed GDI in the adjuvant treatment of angina pectoris, including 41 randomized controlled trials involving 4,462 patients.…”
Section: Myocardial Infarction and Cardiomyopathymentioning
confidence: 99%
“…Danhong Injection (DHI) is composed of Salviae Miltiorrhizae Radix et Rhizoma, known as Danshen in Chinese (DS), and Carthami Flos, known as Honghua in Chinese (HH). DHI exhibits effects such as antiplatelet coagulation, anti-inflammation, antioxidation, and antiapoptosis. , DHI is commonly used for the prevention and treatment of cardiovascular and cerebrovascular diseases. , However, further research is needed to investigate the effective active compounds and key mechanisms of action of DHI on BD-CI/R.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 DHI is commonly used for the prevention and treatment of cardiovascular and cerebrovascular diseases. 15 , 16 However, further research is needed to investigate the effective active compounds and key mechanisms of action of DHI on BD-CI/R.…”
Section: Introductionmentioning
confidence: 99%
“…DHI has anti-atherosclerosis, inhibiting platelet aggregation ( Li et al, 2022 ), improving microcirculation, promoting fibrinolysis, and even has a certain anticoagulant effects ( Feng et al, 2019 ). Research has shown that DHI is superior to Western medicine in terms of incidence of adverse cardiac reactions, promotion of reperfusion, improvement of heart function, and protection of myocardium ( He et al, 2021 ). However, there is limited literature review and systematic review on the treatment of MI with DHI, which requires further research.…”
Section: Introductionmentioning
confidence: 99%